2023
DOI: 10.3389/fpls.2023.1114611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen application on winter wheat growth, water use, and yield under different shallow groundwater depths

Abstract: Shallow groundwater plays a vital role in physiology morphological attributes, water use, and yield production of winter wheat, but little is known of its interaction with nitrogen (N) application. We aimed to explore the effects of N fertilization rate and shallow groundwater table depth (WTD) on winter wheat growth attributes, yield, and water use. Experiments were carried out in micro-lysimeters at WTD of 0.6, 0.9, 1.2, and 1.5 m with 0, 150, 240, and 300 kg/ha N application levels for the winter wheat (Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Excess nitrogen may stimulate the growth of vegetative parts of the plant, although in this study the difference in stem and leaf weight was not significant. She et al (2023) reported that nitrogen consumption of more than 150 to 240 kg per hectare not affect wheat grain yield and growth. Spike length had a significantly positive correlation with most of the studied traits (Table 3).…”
Section: Stem and Leaf Weight And Spike Lengthmentioning
confidence: 99%
“…Excess nitrogen may stimulate the growth of vegetative parts of the plant, although in this study the difference in stem and leaf weight was not significant. She et al (2023) reported that nitrogen consumption of more than 150 to 240 kg per hectare not affect wheat grain yield and growth. Spike length had a significantly positive correlation with most of the studied traits (Table 3).…”
Section: Stem and Leaf Weight And Spike Lengthmentioning
confidence: 99%